2022
DOI: 10.3389/fonc.2022.822902
|View full text |Cite
|
Sign up to set email alerts
|

Interim Analysis of Impact of Adding Low Dose Pulmonary Radiotherapy to Moderate COVID-19 Pneumonia Patients: IMpaCt-RT Study

Abstract: BackgroundTreatment for coronavirus disease 2019 (COVID-19) pneumonia remains largely supportive till date and multiple clinical trials took place within the short span of time to evaluate the role of investigational therapies. The anti-inflammatory effect of low dose whole lung radiation in treating pneumonia has been documented earlier. This clinical trial analyzed the effect of low dose radiation therapy (LDRT) in a moderately affected COVID-19 pneumonia patient cohort and has evaluated its effect in stoppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
5
0
3
Order By: Relevance
“…LDRT showed real curative benefits in the management of a variety of clinical conditions in which inflammation plays an important role, such as epicondylitis [15], osteoarthritis [16], necrotizing abscesses [17], and pneumonia. Several studies show that LDRT improves respiratory parameters and lung involvement and reduces serum inflammation markers [13,[18][19][20]. A comparative cohort study reported a reduction in mortality among moderate COVID-19 patients treated with LDRT compared to the control group [21].…”
Section: Discussionmentioning
confidence: 99%
“…LDRT showed real curative benefits in the management of a variety of clinical conditions in which inflammation plays an important role, such as epicondylitis [15], osteoarthritis [16], necrotizing abscesses [17], and pneumonia. Several studies show that LDRT improves respiratory parameters and lung involvement and reduces serum inflammation markers [13,[18][19][20]. A comparative cohort study reported a reduction in mortality among moderate COVID-19 patients treated with LDRT compared to the control group [21].…”
Section: Discussionmentioning
confidence: 99%
“…The authors conducted a prospective comparative cohort study to evaluate the clinical efficacy of LDWLI in moderate-to-severe COVID-19 pneumonia. We congratulate Ortiz et al for their inspiring conclusions and for having the largest sample size in this research [1] , [2] , [3] , [4] , [5] , [6] , [7] . However, some potential pitfalls should be addressed before we proceed with this evidence for clinical practice and research.…”
mentioning
confidence: 79%
“…Low-dose whole-lung irradiation (LDWLI), a novel potential therapy of coronavirus disease 2019 (COVID-19) pneumonia, is a readily available modern medical resource worldwide [1] . Many clinical trials have been conducted to investigate the efficacy of LDWLI in reducing the COVID-19-related mortality risk [1] , [2] , [3] , [4] , [5] , [6] , [7] . As per our knowledge, the study published in the Green Journal by Ortiz et al [2] has the largest sample size among similar studies published to date [1] , [2] , [3] , [4] , [5] , [6] , [7] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that addressing these issues would be beneficial to further enhance the value of the study. Moreover, several eligible and crucial studies have been published 7 , 8 , 9 , 10 that were not analyzed in the article. Therefore, a timely, updated meta-analysis should be carried out to provide more determinate evidence for decision making and for ongoing clinical trials.…”
mentioning
confidence: 99%